1998
DOI: 10.1114/1.36
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Real-Time Aortic Segmental Volume Using the Conductance Catheter

Abstract: The goal of this investigation was to determine if the conductance catheter technique for chamber volume measurement could be applied in vivo to determine real-time phasic aortic segmental volume. A four-electrode conductance catheter was used to measure time-varying resistance of the descending thoracic aorta in open-chest, anesthetized dogs. Resistance was converted to segmental volume and the slope correction factor (alpha) and parallel conductance volume (Vp) were determined. The results showed excellent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In blood vessels, Hettrick et al (12) showed that the value of ␣ is near unity for small cylinders (Ͻ10 mm in diameter) in a finite-element simulation and in in vitro measurements. Finally, the value of ␣ deviates from unity primarily under in vivo conditions because of the presence of blood cells (13). Again, our proposed methodology eliminates the effect of blood cells in vivo during the transient injections.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In blood vessels, Hettrick et al (12) showed that the value of ␣ is near unity for small cylinders (Ͻ10 mm in diameter) in a finite-element simulation and in in vitro measurements. Finally, the value of ␣ deviates from unity primarily under in vivo conditions because of the presence of blood cells (13). Again, our proposed methodology eliminates the effect of blood cells in vivo during the transient injections.…”
Section: Discussionmentioning
confidence: 89%
“…THE CONDUCTANCE CATHETER METHOD, which has been used previously to measure ventricular volume (4 -5, 7, 14 -16, 29, 30, 33), has recently been adapted to determine the crosssectional area (CSA) of the aorta (11)(12)(13). The conductance catheter technique is based on a cylindrical model by measuring the electrical impedance of the blood with two outer electrodes for excitation and two inner electrodes for detection to yield the CSA of the chamber of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic features of tissue electrical conductivity also affect parallel conductance. In fact, parallel conductance has been treated as a potential source of offset in conductance measurements [6,[8][9][10][12][13][14]. In addition, the parallel conductance mediated by heterogeneous electrical properties of aortic wall has been examined in terms of aortic diameter measurements [12].…”
Section: Introductionmentioning
confidence: 99%
“…The conductance catheter has been widely adopted for sizing the chamber volume of ventricles [1 -5] and the luminal diameter of aorta [6,7] and medium-size arteries [8 -11]. Two bolus injections of saline solutions with known electrical conductivities (e.g.…”
Section: Introductionmentioning
confidence: 99%